Central Obesity as a Risk Factor for Low Back Pain - Putri, Reny Arienta; Setiorini, Anggi; Mayasari, Diana; Mustofa, Syazili (Medula, 2024)
Central obesity, or abdominal obesity, is a condition marked by excessive fat accumulation around internal organs, leading to a variety of health complications such as cardiovascular disease, type 2 diabetes, and musculoskeletal disorders, including low back pain (LBP). Central obesity is defined by increased waist circumference, with values greater than 80 cm in women and 90 cm in men. The condition is primarily influenced by factors such as physical inactivity, poor eating habits, and aging. The relationship between central obesity and LBP is supported by studies indicating that abdominal fat increases mechanical load on the lumbar spine, contributing to disc degeneration and pain. Additionally, adipose tissue secretes pro-inflammatory cytokines that exacerbate inflammation and pain sensitization in the spine, leading to LBP. Obesity-related complications, such as muscle weakness and sleep disturbances, can further reduce quality of life. Preventive measures for LBP include physical exercise, weight reduction, and posture correction. Effective treatment options range from pharmacological therapies to physical rehabilitation and alternative medicine approaches. Understanding the link between central obesity and LBP is critical in developing preventive strategies and improving the management of this common condition.